A response to 'One Christ—Many Witnesses: Vision of Mission and Unity, Edinburgh and Beyond'. (October 2016) - Behera, Marina Ngursangzeli
A short response to 'One Christ—Many Witnesses: Vision of Mission and Unity, Edinburgh and Beyond' by Dana Robert.